Lineage Determination as a Rights-Restoration Mechanism for Children: An Analysis of Judicial Reasoning and Its Legal Implications - Khairizzaman Khairizzaman; Mansari Mansari; Nufiar Nufiar; Dedy Sumardi; Mukhsin Nyak Umar; Muhammad Yusuf (Program Pascasarjana IAIN Langsa, 2026)
Children born from unregistered marriages continue to occupy a legally vulnerable position within Indonesian family law. Existing studies predominantly examine the civil consequences of unregistered marriages or the administrative status of children, while limited attention has been given to how judicial reasoning constructs legal protection through the determination of a child’s lineage. This study addresses that gap by analyzing the legal foundations and judicial construction employed in parentage determination petitions and their implications for strengthening child protection within Islamic family law. The research applies a qualitative legal method using normative and empiris, conceptual, and case approaches through the examination of court decisions, statutory regulations, and legal doctrine. The data were collected through interviews with Religious Court judges and documentary analysis. The findings reveal that judges do not merely verify biological relationships but develop a child-centered legal construction by integrating the principle of the best interests of the child with Islamic legal requirements concerning the validity of marriage and evidentiary standards. Judicial assessment of witnesses, documentary evidence, and trial facts functions as a mechanism for transforming factual parent-child relationships into legally recognized civil status. This study argues that the determination of lineage serves as a juridical instrument of rights restoration, creating a protective framework that secures inheritance rights, maintenance, guardianship, and civil registration while reducing the adverse effects of legal uncertainty arising from unregistered marriages. The research contributes a conceptual model of lineage determination as a child protection mechanism that bridges Islamic family law principles, evidentiary law, and contemporary child rights standards.